Evaluasi Penggunaan Obat pada Pasien Rawat Inap Skizofrenia Paranoid di RSI Banjarnegara Tahun 2024 - Kholid, Rofik; Dewi, Iva Rinia; Dewi, Hika Dwi Kartina (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Paranoid schizophrenia, the most common form of schizophrenia characterized by delusions and hallucinations, is typically treated with antipsychotic medications. This research aimed to evaluate the medication use in 75 patients with paranoid schizophrenia at RSI Banjarnegara by adhering to the "5T" principles: correct diagnosis, patient, medication, dosage, and treatment duration. Methods: This study employed a descriptive observational approach. Retrospective data was collected by gathering medical records of paranoid schizophrenia patients admitted to the Inpatient Unit of RSI Banjarnegara throughout the year 2024. Results: The results show that the most widely used medication was Risperidone 2 mg, prescribed to 31 patients (41.3%). This was followed by Clozapine 25 mg, used by 20 patients (26.7%). The most common combination drug was Risperidone 2 mg and Clozapine 25 mg, administered to 7 patients (9.3%). Conclusion: The evaluation of drug use in paranoid schizophrenia patients demonstrated that all "5T" principles were met, with 100% correctness in diagnosis, patient identification, drug selection, dosage, and duration of administration.